Pharmacokinetics of lopinavir/ritonavir and efavirenz in food insecure HIV‐infected pregnant and breastfeeding women in tororo, uganda. (21st September 2013) - Bartelink, Imke H.; Savic, Rada M.; Mwesigwa, Julia; Achan, Jane; Clark, Tamara; Plenty, Albert; Charlebois, Edwin; Kamya, Moses; Young, Sera L.; Gandhi, Monica; Havlir, Diane; Cohan, Deborah; et al.
Abstract Pregnancy and food insecurity may impact antiretroviral (ART) pharmacokinetics (PK), adherence and response. We sought to quantify and characterize the PK of lopinavir/ritonavir (LPV/r) and efavirenz (EFV) by pregnancy and nutritional status among HIV‐infected women in Tororo, Uganda. In 2011, 62/225 ante‐partum/post‐partum single dried blood spot samples DBS and 43 post‐partum hair samples for LPV/r were derived from 116 women, 51/194 ante‐/post‐partum DBS and 53 post‐partum hair samples for EFV from 105 women. Eighty percent of Ugandan participants were severely food insecure, 26% lost weight ante‐partum, and median BMI post‐partum was only 20.2 kg/m2. Rich PK‐data of normally nourished (pregnant) women and healthy Ugandans established prior information. Overall, drug exposure was reduced (LPV −33%, EFV −15%, ritonavir −17%) compared to well‐nourished controls (P < 0.001), attributable to decreased bioavailability. Pregnancy increased LPV/r clearance 68% (P < 0.001), whereas EFV clearance remained unchanged. Hair concentrations correlated with plasma‐exposure (P < 0.001), explaining 29% PK‐variability. In conclusion, pregnancy and food insecurity were associated with lower ART exposures in this cohort of predominantly underweight women, compared to well‐nourished women. Much variability in plasma‐exposure was quantified using hair concentrations. Addressing malnutrition as well as ART‐PK in this setting should be a priority.